DNA metabarcoding to assess diet partitioning and feeding strategies in generalist vertebrate predators: a case study on three syntopic lacertid lizards from Morocco. (21st May 2019) - Pereira, Ana; Xavier, Raquel; Perera, Ana; Salvi, Daniele; Harris, D James
Abstract: DNA metabarcoding is a fast and simple alternative to traditional microscopy methods, which have been the main tool for identification of prey in dietary studies of lizards. In this study, we applied a metabarcoding approach based on COI and 16S rRNA amplicons to assess diet partitioning and feeding strategies in three syntopic lizards from Taza, Morocco: Scelarcis perspicillata chabanaudi, Scelarcis perspicillata pellegrini and Podarcis vaucheri . In order to avoid competition, these lizards are expected to consume different prey species because they occupy distinct trophic niches, use different foraging strategies and express different dorsal pigmentation patterns. Given the spotted pattern of S. p. chabanaudi, we hypothesize a sit-and-wait foraging strategy with a less diverse diet and a higher consumption of mobile prey relative to the striped S. p. pellegrini and P. vaucheri which, as potential active foragers, are expected to have a higher diet diversity. Previous diet assessments using microscopy on faecal remains seem to contradict these expectations. Our results show that, as expected, the diet of S. p. chabanaudi is less diverse than the diet of S. p. pellegrini . Regarding P. vaucheri, our dietary data are consistent with the hypothesis that this species behaves as an active forager, owing to its high niche overlap with S. p. pellegrini . Advantages and limitations of molecular barcoding compared with the microscopy approach to the analysis of lizard diets are discussed.